2019
DOI: 10.1186/s13643-019-1125-2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic measures of movement impairment, repositioning, and posture in people with and without neck pain—a systematic review

Abstract: Background Neck pain is a major public health problem. Our objective was to describe differences in measures of movement and posture between people with and without neck pain. Methods PubMed and Embase were searched before 15 February 2019 for studies comparing people with neck pain with controls using electronic measurements of neck movement and/or posture. Data were extracted on participants, device, test methods, active range of motion (RoM) and quality of motion, jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 74 publications
3
33
0
Order By: Relevance
“…Ten years ago, those were the most important properties but in reverse order. Quantity of angle seems decreased in neck pain patients 14 compared with healthy subjects and is recommended as a physical examination measure related to clinical prognosis. However, there is a weak correlation between quantity of angle and disability 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten years ago, those were the most important properties but in reverse order. Quantity of angle seems decreased in neck pain patients 14 compared with healthy subjects and is recommended as a physical examination measure related to clinical prognosis. However, there is a weak correlation between quantity of angle and disability 19 .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although a large cohort study recommended to not consider cervical range of movement (CROM) as indicator to measure the progress of chronic neck pain 13 a systematic review reported reduced active CROM in people with neck pain compared with healthy subjects. 14 Also, PAM tests such as cranio-cervical flexion test, neck muscles endurance tests and JPE tests have moderate evidence for use in patients with non-specific neck pain 1,2 and have been shown to exhibit acceptable reliability and validity during the clinical examination. 8 A previous survey study conducted over 10 years ago 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though these approaches seem promising, economic measurement systems are needed for reliable, valid, and objective ongoing monitoring, for example during computer work or gaming. Existing IMU models measure the angles of the neck accurately to some extent, but none of these models include an estimate of translation which would be important for the study of forward head postures [34][35][36]. In contrast, camera-based systems limit a persons' range of motion because the person must always act within the field of view of the cameras [32,34,37].…”
Section: Identifying Malpositionmentioning
confidence: 99%
“…Chronic whiplash and tension‐type headache were studied together since these conditions are clinically similar by having chronic muscular pain and tenderness in the neck. Previous studies have indicated dyscoordination of head movements in whiplash and in chronic neck pain conditions as measured by various methods such as “Fastrak” and the “Fly” 1‐7 and reviewed by Hesby et al 8 Recently, an additional “clinical cervical movement sense” test involving head laser tracking of a “ZZ” like figure was used to measure head movements in chronic neck pain and monitor a possible effect of training 9 . While it appears that each of these methods may have good reliability within the local settings of the respective studies, these methods are not easily standardizable nor transferable for comparison in other clinical settings.…”
Section: Introductionmentioning
confidence: 99%